Immunophenotypic analysis reveals heterogeneity and common biologic aspects in monoclonal B‐cell lymphocytosis. Issue 4 (23rd December 2014) - Kostopoulos, Ioannis V.; Paterakis, Georgios; Papadimitriou, Konstantinos; Pavlidis, Dimitrios; Tsitsilonis, Ourania E.; Papadhimitriou, Stefanos I.
<x xml:space="preserve">Abstract</x> Monoclonal B‐cell lymphocytosis (MBL) is the presence of small B‐cell clones in the peripheral blood of healthy subjects. Most MBL have the characteristic phenotype of chronic lymphocyte leukemia (chronic lymphocytic leukemia (CLL)‐like MBL), and depending on the number of monoclonal B‐cells, may characterize a preclinical stage of the CLL. However, there are also MBL with an atypical (CD5+CD20+/brightCD23dim/−) or a CD5neg phenotype, which remain largely unexplored. We performed an extended immunophenotypic, cytogenetic, and hematologic analysis in 75 CLL‐like, 39 atypical, 50 CD5neg, and 7 biphenotypic MBL cases to detect differences or similarities among the MBL subsets. The phenotypic analysis showed expression variations in many surface markers and a wide spectrum of disease‐specific phenotypes within each MBL subtype. Interphase fluorescent in situ hybridization analysis showed a different panel of aberrations according to the phenotype. Overall, del(13q14) and +12 were the most common abnormalities (39%), whereas del(11q13), del(17p13), and del(6q23) were detected only in 3, 1, and 0 cases, respectively. A comparison of MBL with overt chronic lymphoproliferations revealed common aspects in the preclinical state, regarding both the kind of cytogenetic aberrations detected and the lymphocyte composition. Our findings highlight not only the heterogeneity among MBL subsets but also indicate common biologic features which differentiate MBL from clinical disease. © 2014 Wiley Periodicals, Inc.